KOSAKATA BUAH-BUAHAN LOKAL DALAM BAHASA DAYAK BAKATI DIALEK RARA DI BENGKAYANG - Krismonika, Krismonika; Patriantoro, Patriantoro; Muzammil, Ahmad Rabiul (Universitas Tanjungpura, 2025)
This study aims to find out and explain the vocabulary of local fruits in the Dayak Bakati language of the Raran dialect in Bengkayang. This research is qualitative with a descriptive method. The data collection techniques used include observation techniques, interview techniques, recording techniques, record techniques, and documentation techniques. The researcher's data collection tool is a key instrument and is assisted by other equipment such as question lists, mobile phones, and stationery. The source of data in this study is the Dayak Bakati language, the Rara dialect in Bengkayang which is spoken by residents of Pejampi Hamlet, Mayak Village, Seluas District. The data of this study are all vocabulary of local fruits in the Dayak Bakati language of the Rara dialect in Bengkayang. The results of this study showed that 51 local fruit vocabulary was found in the form of terms consisting of 43 data based on monomorphic forms (single words) and there were 8 data based on polymorphemic. Furthermore, based on the type of meaning and function in the vocabulary of local fruits, 51 vocabulary words have lexical meanings, 16 vocabulary words have cultural meanings, and 51 functions of local fruits.